A new household ultrasonic cleaning method for pyrethroids in cabbage - Chengwei Yu; Xu Huang; Yawei Fan; Zeyuan Deng (Food Science and Human Wellness)
Pyrethroid is widely used in developing countries and is a potential threat to human health. So putting forward an effective pyrethroid cleaning method is of vital importance. Clearance of fenpropathrin, cypermethrin and deltamethrin in cabbage by using ultrasonic treatment accompanied with different baking soda concentrations were investigated in this study. The results of response surface methodology showed that the maximum clearance rate was 70.61% for fenpropathrin under the optimal power, treated time, treated temperature and baking soda concentration, which were 260.02 W, 10 min, 20.15 °C and 0.014 g/mL, respectively. Similarly, the maximum removal efficiency was 73.72% for cypermethrin under 240 W, 13.84 min, 19.53 °C and 0.014 g/mL, and 92.15% for deltamethrin under 238.99 W, 12.42 min, 25 °C and 0.013 g/mL. The clearance rate of pyrethroid by this method was significant higher (P < 0.05) than traditional cleaning methods (bathing and running water washing). The contents of the compositions such as vitamin C, total soluble sugar, protein and dietary fiber, texture and sensory evaluation of cabbage were not found obvious changes after the ultrasonic treatment combined with baking soda (P > 0.05). Results showed that ultrasonic treatment combined with baking soda was an effective way to eliminate the fenpropathrin, cypermethrin and deltamethrin in cabbage without influencing cabbage quality.